Telomere length and physical performance at older ages: an individual participant meta-analysis. - Michael P Gardner; Carmen Martin-Ruiz; Rachel Cooper; Rebecca Hardy; Avan Aihie Sayer; Cyrus Cooper; Ian J Deary; John Gallacher; Sarah E Harris; Paul G Shiels; John M Starr; Diana Kuh; et al. (PLoS ONE)
Background Telomeres are involved in cellular ageing and shorten with increasing age. If telomere length is a valuable biomarker of ageing, then telomere shortening should be associated with worse physical performance, an ageing trait, but evidence for such an association is lacking. The purpose of this study was to examine whether change in telomere length is associated with physical performance. Methods Using data from four UK adult cohorts (ages 53-80 years at baseline), we undertook cross-sectional and longitudinal analyses. We analysed each study separately and then used meta-analytic methods to pool the results. Physical performance was measured using walking and chair rise speed, standing balance time and grip strength. Telomere length was measured by quantitative real-time polymerase chain reaction (PCR) in whole blood at baseline and follow-up (time 1, time 2). Results Total sample sizes in meta-analyses ranged from 1,217 to 3,707. There was little evidence that telomere length was associated with walking speed, balance or grip strength, though weak associations were seen with chair rise speed and grip strength at baseline (p = 0.02 and 0.01 respectively). Faster chair rise speed at follow-up, was associated with a smaller decline in telomere length between time 1 and time 2 (standardised coefficient per SD increase 0.061, 95% CI 0.006, 0.115, p = 0.03) but this was consistent with chance (p =0.08) after further adjustment. Conclusions Whereas shortening of leukocyte telomeres might be an important measure of cellular ageing, there is little evidence that it is a strong biomarker for physical performance.